The Influence of Intrinsic and Extrinsic Factors on Husband's Participation Using Contraception in Sitinjo District, Dairi Regency - Risdiana Melinda Naibaho; Rugun Togianur Lingga (Institute of Computer Science (IOCS), 2021)
The role of eife in the family is also expected to be improved by giving motivation to the husband to choose and use effective birth control. Therefore Family Planning (KB) became one of the efforts to suppress the population. One of the efforts that promoted family planning is a contraceptive in men, but the husband's participation in family planning is very low. Husband's low participation in the use of contraceptives Men are caused by many factors, among others, intrinsic factors such as knowledge and attitudes husband husband and extrinsic factors, namely access to family planning services and wife attitude. This type of research is analytic survey with explanatory approach. The population is all spouses of fertile age husband who resides in the village of Sitinjo II District Sitinjo Dairi as many as 382 people. Sampling with simple random technique as much as 79 people. Techniques of collecting data through interviews using a questionnaire. Data were analyzed using univariate, bivariate with chi square, multivariate logistic regression using SPSS 19. Results of this study indicate that factors husband attitude (p-value 0.026), access to family planning services (p-value 0.038), the attitude of the wife (p-value 0.034), influence of the husband's participation using contraception, while knowledge (p-value 0.251) , does not affect the use of contraceptives husband. The most influencing factor is access to family planning services. Advice to health workers in the office of Women's Empowerment, Child and Family Planning (PPAKB), health centers and the field officers in the field, to improve family planning services for men on through Communication. The information and education and increase partnerships with professional organizations, community leaders and religious leaders, so expect these leaders will participate disseminate information to the public and to develop family planning group of men as a communication medium to increase male participation in family planning and reproductive health is expected to make the group as a motivator Familly Planning.